A Comparative Study on the Curative and Regenerative Response of Megascolex konkanensis Towards Three Traditionally used Herbal Remedies - Varghese, Roslin; Sailesh, Kumar Sai; Joy, Ayana; J K, Mukkadan (Biology, Engineering, Medicine and Science Reports)
Background: To evaluate the wound healing efficacy of some plants in the regeneration of earthworms. The present study was taken up to compare the curative and regenerative responses of Megascolex konkanensis towards the phyto extracts prepared from Ocimum sanctum, Curcuma longa and Scoparia dulcis. Objective: To assess the wound healing property of three plant extract at different concentrations. Materials and method: During the period of study the collected earthworms were separated into 4 groups of 2 organisms each in the paper cups, labeled and kept safely. In the time of experiment the 55th segment of posterior clitellum of each earthworm was cut carefully with the help of scissors. Result: The day 9, the earthworms treated with Scoparia dulcis extracts started showing faster growth compared with Ocimum sanctum, Curcuma longa, and control. Scoparia dulcis extract caused significant greater wound healing property than other two phyto extracts. The overall observation depicts that the extracts significantly promoted the healing process, as evident by an increased rate of regeneration in worms treated with herbal extract, suggesting the possible utilization of this plant to enhance wound healing.
Keywords: Wound healing; Earthworms; Plant extract; Ocimum sanctum; Curcuma longa and Scoparia dulcis